PEMBINAAN PRESTASI ATLET WUSHU SANDA JAWA TENGAH MENUJU JUARA (Indonesian Journal for Physical Education and Sport, 2021)
Achievement coaching is a measure of the success of an athlete to become a champion. Thus, the role of government is very important in supporting an athlete to perform optimally. In government support such as emotional support, reward support, infrastructure support and supplementary support greatly affects the performance of an athlete in the world of sports. The focus of the problem in this research is the extent to which the development of achievements carried out by the government from the city to the national level. The purpose of this study was to describe and conclude the development of the achievements of the wushu sanda athletes in Central Java to become champions. This research is a descriptive study with data collection techniques through observation and documentation. Analyze data through life experiences. The sample in this study were the athletes of the Central Java sanda wushu.